Penerapan Prinsip Kehati-Hatian Bank pada Hapus Buku dan Hapus Tagih Kredit Macet bagi Usaha Mikro dan Kecil Ditinjau dari Undang-Undang No. 4 Tahun 2023 tentang Pengembangan dan Penguatan Sektor Keuangan - Illona Novira Elthania; Tarsisius Murwadji; Etty Mulyati (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
. Regulation of Law no. 4 of 2023 concerning Development and Strengthening of the Financial Sector is used as a regulatory for banks in general in carrying out write-offs and write-offs, especially for MSE debtors. Seeing that post-Covid-19 conditions have made the business of MSE debtors even worse, banks have attempted to restructure credit affected by Covid-19 to reduce the bank's NPL ratio as a reference for the bank's health. However, when the reconstruction is not successful, the bank can carry out a conditional write-off and absolute write-off program as a solution to bad credit. In carrying out write-offs, the Bank writes off the total value of productive assets that cannot be collected from the balance sheet and recorded in the administrative account/off balance sheet. The act of write-off does not eliminate the bank's right to collect from its debtors, but the bank will continue to try to collect from its debtors until the credit the bank has provided can be paid in full. The aim of this research is to complete the settlement of bad debts through conditional write-offs and absolute write-off for the PPSK Law. This type of research uses normative juridical research. The types of data used in this research are primary legal materials, secondary legal materials and tertiary legal materials. Data collection techniques using literature studies and field studies. The results of this research are that there are no provisions that regulate in detail the procedures for writing off and writing off bad debts for banks. This is addressed through each bank's internal policy which regulates procedures for write-offs and write-offs for MSE debtors.